Unveiling the Nexus between Bank-Specific Factors, Macroeconomic Indicators, and Commercial Bank Performance - Pathak, Hari Prasad (PYC Nepal Journal of Management, 2023)
This study investigates the performance determinants in Nepalese commercial banks, focusing on both profitability and efficiency scores. Employing a quantitative research approach, panel data from the financial reports of all 28 commercial banks in Nepal from 2008 to 2019 is analyzed. Regression analysis, including fixed and random effect models determined by the Hausman test, is utilized to examine the impact of bank-specific factors and macroeconomic indicators on bank performance. Additionally, data envelopment analysis is employed to measure bank efficiency levels. Findings suggest moderate performance levels with observed improvements in internal management practices and credit policies. While significant impacts of bank-specific factors on performance are identified, macroeconomic indicators show limited influence. Specifically, capitalization and management efficiency positively impact profitability and efficiency, while non-performing assets negatively affect both. These findings provide valuable insights for policymakers and bank management to enhance profitability through prudent regulatory measures.